野生核桃仁营养成分及其油脂脂肪酸 组成、热特性分析Nutritional components of wild walnut kernel and fatty acid composition, thermal characteristics of its oil - 韦承珊1,2，毕佳俊1,2，李云仙1,2，刘祥义1,2，徐娟1,2 WEI Chengshan1,2，BI Jiajun1,2，LI Yunxian1,2，LIU Xiangyi1,2，XU Juan1,2 (Zhongguo youzhi, 2024)
为促进野生核桃的综合开发利用，以云南省临沧市野生核桃为原料，测定了核桃仁粗脂肪、粗蛋白质含量，核桃仁粕氨基酸组成、矿质元素含量，以及核桃油的生育酚含量、总脂肪酸及sn-2位脂肪酸组成，并分析了其热特性。结果表明：野生核桃仁中粗脂肪含量为44.04%，粗蛋白质含量为2163%；核桃仁粕中7种人体必需氨基酸占氨基酸总量的31.47%，9种药用氨基酸占氨基酸总量的70.97%；核桃仁粕中含有丰富的矿质元素，属于高钾低钠食品，微量元素中Mn元素含量最高，为144.8 μg/g，重金属元素未检出；野生核桃油主要由7种脂肪酸组成，其中sn-2位多不饱和脂肪酸含量（7001%）高于总脂肪酸中多不饱和脂肪酸含量（61.48%）；核桃油中γ-生育酚含量最高，为510.10 mg/kg；核桃油低温结晶主要在-30 ℃和-13 ℃熔融，其快速热解温度为317~470 ℃，在416 ℃质量损失速率绝对值达到最大。野生核桃仁营养价值较高，具有广泛的开发利用价值。To promote the comprehensive development and utilization of wild walnut, using wild walnut from Lincang, Yunnan as raw material, the contents of crude fat and crude protein of walnut kernel, the amino acid composition and mineral element content of walnut kernel meal, the tocopherol content, total fatty acid composition and sn-2 fatty acid composition of walnut oil were determined, and the thermal characteristics of walnut oil was analyzed. The results showed that the crude fat content of wild walnut kernel was 44.04% and the crude protein content was 21.63%; 7 kinds essential amino acids accounted for 3147% of the total amino acids content and 9 kinds of medicinal amino acids accounted for 70.97% of the total amino acids content; walnut kernel meal was rich in mineral elements, belonging to high potassium and low sodium food, and the content of Mn was 144.8 μg/g, which was the highest in trace elements, and no heavy metal element was detected; wild walnut oil was mainly composed of 7 fatty acids, and the sn-2 polyunsaturated fatty acid content (70.01%) was higher than that in the total fatty acid (6148%); γ-tocopherol content in wild walnut oil was the highest, which was 510.10 mg/kg; the low temperature crystallization of walnut oil mainly melted at -30 ℃ and -13 ℃, and its rapid pyrolysis temperature was 317-470 ℃, and the absolute value of the mass loss rate reached the maximum at 416 ℃. Wild walnut kernel has high nutritional value and extensive exploitation and utilization value.